DETERMINAN PENGGUNAAN METODE KONTRASEPSI JANGKA PANJANG PADA PESERTA KB AKTIF DI WILAYAH KERJA PUSKESMAS KELURAHAN KARET KUNINGAN TAHUN 2021 - Marshaeila Mediana, (2021)
Long acting contraception methods (LACM) is a type of contraception in a family planning program that has high effectiveness and low degree of failure in delaying, spacing and limiting pregnancies. However, the usage still relatively small (21.25%). The purpose of this study is to determine and understanding determinant of the LACM utilization at Public Health Center Karet Kuningan working area and see the dominant factor. This study using cross sectional design with 364 active family planning participants. This study used simple random sampling technique and questionnaire for the instrument. The results of this study indicates that there are 114 family planning participants using LACM (31,3%) from all samples. Determinants that have significant relationship to the use of LACM are knowledge (p-value = 0.000), access information (p-value = 0.000), partner support (p-value = 0.000), occupation (p-value = 0.000) and education (p-value = 0.047). The dominant factor who influenced LACM utilization is access information (p-value = 0.000). The conclusion of this study is the determinants of LACM utilzation are knowledge, information access, partner support, occupation, and education. For health workers, it is suggested to improve and optimize education to the community effectively and efficiently so the coverage of LACM participants will increase.